The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/jce.15391
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical accuracy of the KODEX‐EPD novel 3D mapping system of the left atrium during pulmonary vein isolation: A correlation with computer tomography imaging

Abstract: Background: A novel 3D mapping system (KODEX-EPD, EPD Solutions) enables catheter localization and real-time 3D cardiac mapping.Objective: To evaluate left atrium (LA) anatomical mapping accuracy created by the KODEX-EPD system during pulmonary vein isolation (PVI) compared with gold standard computed tomography (CT) images acquired from the same patients before the procedure.Methods: In 15 consecutive patients who underwent PVI, 3D mapping of the LA was created on the KODEX-EPD system using the Achieve cathet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 10 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…A previous study compared high-density KODEX-EPD mapping versus 3D computed tomography (CT) imaging in mapping the left atrium. This study concluded that the KODEX-EPD system provides an accurate and fast mapping technique with high reliability when utilized in cases of atrial ablation [34].…”
Section: Discussionmentioning
confidence: 75%
“…A previous study compared high-density KODEX-EPD mapping versus 3D computed tomography (CT) imaging in mapping the left atrium. This study concluded that the KODEX-EPD system provides an accurate and fast mapping technique with high reliability when utilized in cases of atrial ablation [34].…”
Section: Discussionmentioning
confidence: 75%
“…The 2 most recent original papers dealing with AF ablation originate from Shaare Zedek Hospital (Jerusalem). Tovia-Brodie and coworkers 135 reported the anatomical accuracy of the KODEX-EPD (Philips, Netherlands) novel 3D mapping system of the left atrium during pulmonary vein isolation and its excellent correlation with computer tomography imaging. In the second paper, Rav Acha and colleagues 136 showed that cryoballoon AF ablation results in circumferential pulmonary vein fibrosis in the majority of pulmonary veins, as assessed by a new clinically relevant magnetic resonance imaging (MRI) analysis.…”
Section: Afl/af Ablationmentioning
confidence: 99%